UJI KIMIAWI DAN BIOLOGI PUPUK ORGANIK CAIR PLUS DARI LIMBAH BAHAN ORGANIK - Eko Hary Agustin Juwaningsih; Nova D. Lussy; Chatlynbi T. Br. Pandjaitan (Partner, 2019)
LOF with JB3 activator from fruit waste (salak, grapes, papaya, banana, pineapple and apple) and market waste (coconut fiber, coconut water) enriched with other organic materials (solid and liquid tofu waste) and added with Trichoderma microbes to increase nutrient content and function of the LOFwith pest and disease controller. The purpose of this study is to get POC plus with JB3 activator with the results of a complete both chemically and biologically (microscopic analysis)analysis. The treatments that were tried were A-1 = POC; A-2 = POC plus; A-3 = POC plus 1; A-4 = POC plus 2. The obtained results are A4 treatment (POC fruit waste, coconut waste on the market, tofu waste and Trichoderma containing C-organic 6.22%, pH 4.37, microbial contaminants ie E.coli <36 Apm / ml and Salmonella sp negative, which is qualifiedbased on fertilizer quality standards of Permentan no 70 / Permentan / SR.140 / 10/2011, but the content of the nutrients (N, P, K, Fe, Mn, Cu and ZN) still classified as soil amenders not yet as liquid organic fertilizer.